2019
DOI: 10.3390/ma12091474
|View full text |Cite
|
Sign up to set email alerts
|

Design of Reinforcement in Nano- and Microcomposites

Abstract: The application of numerical homogenization and optimization in the design of micro- and nanocomposite reinforcement is presented. The influence of boundary conditions, form of a representative volume element, shape and distribution of reinforcement are distinguished as having the crucial influence on a design of the reinforcement. The paper also shows that, in the optimization problems, the distributions of any design variables can be expressed by n-dimensional curves. It applies not only to the tasks of opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In the literature, one can come across broadly discussed research results on the application of carbon-based materials as filler [33][34][35][36].Scientists are also interested in the methods of material optimization, including reinforcement application. The identification and description of the complex structures obtained in this way is a complicated issue [37,38].The research associated with O-ring seals, described in the literature, refers to their reliability. The mechanical behavior of chosen materials, taking into account both static and dynamic strain [38][39][40], is checked during the tests.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, one can come across broadly discussed research results on the application of carbon-based materials as filler [33][34][35][36].Scientists are also interested in the methods of material optimization, including reinforcement application. The identification and description of the complex structures obtained in this way is a complicated issue [37,38].The research associated with O-ring seals, described in the literature, refers to their reliability. The mechanical behavior of chosen materials, taking into account both static and dynamic strain [38][39][40], is checked during the tests.…”
mentioning
confidence: 99%
“…Scientists are also interested in the methods of material optimization, including reinforcement application. The identification and description of the complex structures obtained in this way is a complicated issue [37,38].…”
mentioning
confidence: 99%
“…To reduce the complexity and the cost of optimization process it is necessary to introduce an appropriate parameterization. In References [194,195] it is demonstrated that the distributions of design variables mentioned above can be written as 2D curves representing not only the shape of the edge of the structure or its mid-surface, but also dimensional optimization (e.g., thickness) or topology optimization (distributions: density, volume fraction of the constituents or material with different Young's modulus). The general method of constructing curves on the x-y plane is demonstrated in detail using cubic spline functions of various types and the theoretical introduction is supplemented by the numerical solutions of different problems.…”
Section: Geometric Design Variablesmentioning
confidence: 99%
“…In addition, the increase in temperature inside the stored alternative fuel, as in the case of biological waste treatment processes, is implied by microorganisms that emit heat during the processing of organic matter (contained in biodegradable fractions) [17,18,19,20,21]. Biodegradable fractions are the sum of 100% organic, 100% paper and cardboard, 50% wood, 50% textiles, 40% multimaterial waste, and 30% fine fraction, i.e., waste with a grain size below 10 mm [22].…”
Section: Introductionmentioning
confidence: 99%